Transformation and Educational Management: Challenges and Opportunities for Teacher Professional Development in the Pedagogical Use of Technologies in Costa Rica (Innovaciones Educativas, 2025)
Continuing professional development (CPD) in technology is essential for teachers to meet the current demands of education. Therefore, the objective of this study is to analyze the institutional conditions, participation, and perceived usefulness of CPD activities related to digital technology in the Costa Rican public educational sphere. A quantitative approach with a non-experimental, cross-sectional, and descriptive scope design was used. Furthermore, the sample included n=951 participants, 237 principals and 714 teachers, and a questionnaire with Likert-type scales was applied. The results show that, although some institutional conditions for CPD in technology exist, they are not perceived as accessible or sufficient, especially by the teaching staff. Principals view the training actions promoted by the centers more positively, although optimal levels are not reached. Likewise, the low participation of both groups in the different training modalities is noteworthy, with online courses and collaborative activities being the most used and highly valued. Significant differences in perception between the two groups are identified, suggesting internal gaps in the school's organizational culture. It is concluded that training opportunities still require better planning, monitoring, and contextualization. Finally, it is recommended to strengthen the pedagogical management of leadership teams, as well as allocated space and time for training, and to foster professional collaboration networks.
Keywords: school management; educational technology; school principal; educational management; continuing professional development; knowledge update; digital competence